Pathomorphological features of conjunctival and scleral regeneration associated with intraoperative application of Cyclosporin A - T. A. Zhigalskaya; O. I. Krivosheina; A. N. Dzyman; I. A. Khlusov (Бюллетень сибирской медицины)
Purpose. In experiment in vivo to study the features of regeneration of the conjunctiva and sclera of rats after surgery with intraoperative application of a 0.05% Ciclosporin A.Materials and methods. Еxperimental animals (rats) (n = 48) were divided into the main group, including the subgroups a (n = 16) and b (n = 16) and the comparison group (n = 16). Performed a through cut of the conjunctiva and damage to the surface layers of the sclera one of the eyes of all animals. Further on the surgical trauma zone in the main group, the intraoperative application of the cytostatic was performed. In the subgroup a with a duration of 3 minutes, in the subgroup b – 6 minutes. In the comparison group a hemostatic sponge without a cytostatic was used intraoperatively.Results. In the comparison group postoperative period proceeds with a stereotyped dynamics of cell phase changes in damaged tissues. In the end the development of dense conjunctival-scleral fusion in the area of surgical trauma was noted. Intraoperative application of 0.05% Cyclosporine A leads to a slowing of regeneration, preventing formation of rough conjunctival-scleral scar.Conclusions. Intraoperative applications of 0.05% Cyclosporin A change the stereotyped dynamics of the inflammatory-reparative regeneration in the surgical intervention zone, inhibiting the migration of cells almost in 3 times and significantly (in 2 times) prolonging the duration of the macrophage phase. This causes a slowdown of reparative regeneration, prevents excessive scarring in the operating area.